Evaluation of fetal heart size, morphology and function with fetal growth restriction using fetal HQ - Yunqi Chen; Xiaoli Lv; Lijuan Yang; Dan Hu; Min Ren (BMC, 2024)
Abstract Background Fetal growth restriction (FGR) is associated with various perinatal complications. Limited research has focused on the fetal heart in the context of FGR. This study aimed to investigate the application value of fetal heart quantification (HQ) technology in evaluating the size, morphology, and function of the heart in FGR. Methods A total of 31 fetuses diagnosed with FGR in our hospital from April 2022 to May 2024 were included, alongside another 31 normal fetuses matched for gestational age as the control group. Ultrasound Doppler parameters of the middle cerebral artery (MCA), umbilical artery (UA), venous catheter, and fetal HQ parameters were collected for comparative analysis, and perinatal data were followed up. Results Fetuses with FGR exhibited significant differences in various parameters of the MCA and UA compared to the control group (P < 0.05). The four-chamber view end-diastolic transverse width, end-diastolic area, left ventricular (LV) end-diastolic area, end-systolic area, end-systolic length, end-diastolic volume, end-systolic volume, and right ventricular (RV) end-systolic area in the FGR group were significantly lower than those in the control group (P < 0.05). In the 24-segment analysis, the LV fractional shortening in the FGR group was greater than in the control group at segments 12 to 14, while the end-diastolic diameter (ED) at segments 5 to 13 of the LV and segments 1 to 14 of the RV were smaller than those in the control group, with statistical significance (P < 0.05). Analysis of each subgroup indicated that fractional shortening (FS) in the early-onset group was significantly greater than in the late-onset group at RV segments 2 to 8. LV-ED at segments 1 to 15 and RV-ED at segments 1 to 16 were significantly smaller in the early-onset group than in the control group, and LV ED segments 20 to 21 were significantly smaller in the early-onset group compared to the late-onset group (P < 0.05). FS in the mild group was significantly larger than in the normal group at LV segments 10 to 16. The severe group exhibited significantly smaller LV segment 2 to 11 ED and the mild group showed smaller RV segments 1 to 13 compared to the control group (P < 0.05). Conclusions Fetal HQ is a promising technique for evaluating the cardiac function, size, and morphology in cases of FGR.